British relations with the Malay rulers from decentralization to Malayan independence, 1930-1957 - Smith, Simon C., 1967- (South-East Asian historical monographs., 1995)
From the late nineteenth century Britain's position in the Malay States rested on the fulcrum of indigenous monarchy. Not surprisingly, this aspect of Britain's imperial relationship with Malaya has received close historical attention. The role of the Malay Rulers in the era of decolonization has, nevertheless, been neglected. The assumption has been, especially for the post-war period, that the Rulers' social and political significance declined rapidly. Such interpretations, however, over-simplify the nature of Malayan politics and underestimate the Rulers' role as figureheads of modern Malay nationalism. Indeed, the Malay Rulers survived the departure of the British and have continued to represent a focus of loyalty in competition with the new nationalist parties.